Taxi carpooling model and carpooling effects simulation. (2017) - Zhang, Wei; He, Ruichun; Xiao, Qiang; Ma, Changxi
This paper builds models of two passengers and multiple passengers sharing a taxi. Advantages and effects of taxi carpooling mode are analysed by simulation. The influences of payment ratio and carpool ratio on taxi carpooling effects are analysed. Relevant conclusions are obtained. Simulation results show that taxi carpooling mode can improve driver income, decrease passenger payment and increase passenger capacity obviously. Payment ratio and carpooling ratio have great influences on carpooling effects. Driver income and passenger capacity increase with increase of carpooling ratio. Change of payment ratio influences driver income and passenger payment simultaneously. The increase of carpooling ratio can help to develop carpooling advantages better. Appropriate payment ratio is the key to obtain good carpooling effects. When ρ is larger, appropriate θ can be found to ensure win-win for drivers and passengers, and improve taxi passenger capacity; when ρ is so small that no existing θ can ensure these effects, it needs to increase the number of taxis. These conclusions have a certain guiding significance to formulating taxi policy.